2002
DOI: 10.1177/0022343302039005006
|View full text |Cite
|
Sign up to set email alerts
|

Divided yet United: Israeli-jewish Attitudes Toward the Oslo Process

Abstract: 1 There are, however, other analysts who argue for a trichotomized structure: a large center (60%) and two smaller radical camps at the left (20%) and the right (20%) sides of the political map; e.g. Arian (1999).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 17 publications
1
36
0
Order By: Relevance
“…We also suggest that the mass public will be divided in its views of the foreign leader based on political orientation. Several studies extend the finding that mass foreign policy beliefs are well-structured to publics outside the United States (Hermann and Yuchtman-Yaar 2002;Hurwitz, Peffley, and Seligson 1993;Jenkins-Smith, Mitchell, and Heron 2004). Structure varies across countries, but in general, members of the public can be categorized as positively oriented towards the foreign leader, negatively oriented, or undecided.…”
Section: Conditional Effects Of Public Diplomacymentioning
confidence: 73%
“…We also suggest that the mass public will be divided in its views of the foreign leader based on political orientation. Several studies extend the finding that mass foreign policy beliefs are well-structured to publics outside the United States (Hermann and Yuchtman-Yaar 2002;Hurwitz, Peffley, and Seligson 1993;Jenkins-Smith, Mitchell, and Heron 2004). Structure varies across countries, but in general, members of the public can be categorized as positively oriented towards the foreign leader, negatively oriented, or undecided.…”
Section: Conditional Effects Of Public Diplomacymentioning
confidence: 73%
“…Another question that might be raised regarding the use of ideological orientation as an independent variable in our study is whether this variable is distinct from our dependent variable of opinions regarding peace, given the strong relationship between the two that we and others (Arian, 1995;Hermann & Yuchtman-Yaar, 2002) have observed. As noted above, we believe that the hawkish-dovish dimension represents a stable core aspect of political ideology that parallels other societies, whereas opinions about peace represent a peripheral aspect that is unique to the Israeli context (Jost et al, 2003).…”
Section: Discussionmentioning
confidence: 87%
“…An empirical study of Israelis' opinions about peace during the 1990s and up until 2001 found that while the gap between hawks and doves remained relatively stable over the years, there were also considerable changes over time in the opinions of each group, usually related to salient events and developments in the conflict (Hermann & Yuchtman-Yaar, 2002). This suggests that Israelis' opinions about peace are comprised of two components: one relatively stable that relates to core ideological orientations, and the other more variable and responsive to environmental events.…”
Section: Ideological Orientation Opinions About Peace and Terror Atmentioning
confidence: 99%
See 1 more Smart Citation
“…Very little work has been done in this area. Hermann and Yuchtman-Yaar (2002) introduce a time dimension to the study of Israeli public opinion, using a longitudinal survey. The authors make use of a peace index conducted by the Tami Steinmetz Center for Peace Research, which will also be used in this paper.…”
Section: Public Opinion Formation and Rationalitymentioning
confidence: 99%